2008
DOI: 10.5210/fm.v13i9.2182
|View full text |Cite
|
Sign up to set email alerts
|

Exploring characteristics and effects of user participation in online social Q&A sites

Abstract: People are seeking more meaningful and customized information than what is obtained by keywords-based queries and document retrieval through a search engine. In this paper, we look at a set of such services, referred to as social Q&A sites. With sites such as Google Answers, and primarily Yahoo! Answers, we attempt to understand various characteristics of user participation and their possible effects on the design and success of the site. We discuss these social Q&A sites by comparing their designs bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 0 publications
1
72
1
Order By: Relevance
“…Answers, Answerbag, and WikiAnswers). Reputation is determined by a set of site-specific criteria; a few highly active users on each of these sites only answer questions and do not ask many (Adamic et al, 2008;Shachaf, in press;Shah et al, 2008;Zhang, Ackerman, Adamic, & Nam, 2008). Despite the fact that users can participate in various roles (ask, answer, evaluate, and categorize questions) on these sites simultaneously (Bian et al, 2008), only about one fifth of the users participate in dual roles, asking and responding to questions (Adamic et al, 2008;Shachaf, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Answers, Answerbag, and WikiAnswers). Reputation is determined by a set of site-specific criteria; a few highly active users on each of these sites only answer questions and do not ask many (Adamic et al, 2008;Shachaf, in press;Shah et al, 2008;Zhang, Ackerman, Adamic, & Nam, 2008). Despite the fact that users can participate in various roles (ask, answer, evaluate, and categorize questions) on these sites simultaneously (Bian et al, 2008), only about one fifth of the users participate in dual roles, asking and responding to questions (Adamic et al, 2008;Shachaf, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Answers users based on their experience level and found that users at higher levels tended to be contributors more than consumers, and that they created a disproportionate share of the content and value of the site. However, their efforts did not go unrewarded by the community: Shah et al (2008) observe that while the highest ranking users did not earn as many plaudits for submitting interesting questions as those at lower levels, they did earn more Best Answer designations, and only the latter carries with it point rewards leading to higher levels. High-ranking users may in fact be the most skilled answerers, or they may be more economically rational actors, and employ conscious strategies to maximize their potential reward.…”
Section: Motivation Reputation and Perceived Authoritymentioning
confidence: 99%
“…Are there external factors, such as relationships and communications across other sites, that influence participants' behavior? Shah et al (2008) also identified a challenge common to most comparative studies of SQA sites: extracting comparable data samples. Although Yahoo!…”
Section: Unpack the Track Record Of The Asker And Answerermentioning
confidence: 99%
See 2 more Smart Citations